PENGARUH PEMBELAJARAN PERBANKAN SYARIAH, LITERASI KEUANGAN SYARIAH DAN RELIGIUSITAS TERHADAP MINAT MAHASISWA MENGGUNAKAN PRODUK BANK SYARIAH - Kamila, Shiddiq; ., Rochmawati (Universitas Islam Negeri Alauddin Makassar, 2023)
Obtain a survey to specify the affect of learning Islamic banking, Islamic financial literacy, and religion on student interest in the use of Islamic banking products. This includes quantitative research. The subjects of the survey are FEB students of Surabaya State University who studied Islamic banks or Islamic financial institutions. Sampling by sampling method using Slobin formula with the number of samples as many as 104 respondents. The data collected from the survey will continue with tests using multiple linear regression analysis techniques. Islamic banking learning, Islamic financial literacy, and religiousness simultaneously or partially influence student interest in the use of Islamic banking products with a significance score of 0.00 or higher. 0.05. The result of the R square is 0.461. This means that impact of three independence variables is 46.1%, with the remaining 53.9% being due to variables other than this survey.